Age-Related Regeneration of Osteochondral and Tibial Defects by a Fibrin-Based Construct in vivo - Feng, Xue (Front Bioeng Biotechnol, 2020)
Tissue–biomaterial interactions in different microenvironments influence significantly the repair and regeneration outcomes when a scaffold or construct is implanted. In order to elucidate this issue, a fibrin gel filled macroporous fibrin scaffold (fibrin-based scaffold) was fabricated by loading fibrinogen via a negative pressure method, following with thrombin crosslinking. The macroporous fibrin scaffold exhibited a porous structure with porosity of (88.1 ± 1.3)%, and achieved a modulus of 19.8 ± 0.4 kPa at a wet state after fibrin gel filling, providing a suitable microenvironment for bone marrow-derived mesenchymal stem cells (BMSCs). The in vitro cellular culture revealed that the fibrin-based scaffold could support the adhesion, spreading, and proliferation of BMSCs in appropriate cell encapsulation concentrations. The fibrin-based scaffolds were then combined with BMSCs and lipofectamine/plasmid deoxyribonucleic acid (DNA) encoding mouse-transforming growth factor β1 (pDNA-TGF-β1) complexes to obtain the fibrin-based constructs, which were implanted into osteochondral and tibial defects at young adult rabbits (3 months old) and aged adult rabbits (12 months old) to evaluate their respective repair effects. Partial repair of osteochondral defects and perfect restoration of tibial defects were realized at 18 weeks post-surgery for the young adult rabbits, whereas only partial repair of subchondral bone and tibial bone defects were found at the same time for the aged adult rabbits, confirming the adaptability of the fibrin-based constructs to the different tissue microenvironments by tissue-biomaterial interplays.